PERAN OTORITAS JASA KEUANGAN (OJK) PADA PERBANKAN SYARIAH DI INDONESIA (PRESPEKTIF HUKUM ISLAM) - Umul Nuraini (Fakultas Syariah IAI Al-Khoziny Buduran Sidoarjo, 2026)
This study examines the role of the Financial Services Authority (OJK) in regulating and supervising Islamic banking in Indonesia and analyzes its relevance from the perspective of Islamic law. Employing a normative juridical method through statutory and conceptual approaches, this research reviews OJK regulations, Islamic banking statistical data, and relevant fiqh muamalah concepts, particularly the doctrines of hisbah and maqasid al-shari'ah. The findings indicate that OJK performs regulatory, prudential supervision, and consumer protection functions that structurally correspond to the hisbah institution in classical Islamic legal tradition. Substantively, OJK's Islamic banking regulations can be analyzed through the maqasid al-shari'ah framework, especially hifz al-mal (preservation of wealth) and hifz al-'aql (preservation of intellect). Under OJK's supervision, total Islamic banking assets in Indonesia reached IDR 1,028.18 trillion in October 2025, growing 11.34% year-on-year, the highest achievement in the industry's history. Nevertheless, fragmentation between OJK's prudential supervision and the Sharia Supervisory Board's religious oversight remains a structural challenge requiring an integrated supervisory architecture grounded in maqasid al-shari'ah.